2021
DOI: 10.1186/s41232-021-00177-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesized HMGB1 peptide attenuates liver inflammation and suppresses fibrosis in mice

Abstract: The liver has a high regenerative ability and can induce spontaneous regression of fibrosis when early liver damage occurs; however, these abilities are lost when chronic liver damage results in decompensated cirrhosis. Cell therapies, such as mesenchymal stem cell (MSC) and macrophage therapies, have attracted attention as potential strategies for mitigating liver fibrosis. Here, we evaluated the therapeutic effects of HMGB1 peptide synthesized from box A of high mobility group box 1 protein. Liver damage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In this model, the reduction of liver damage was observed during the first week of treatment, and the reduction of liver damage and improvement of fibrosis was observed in the second week. In addition, single‐cell RNA analysis of hematopoietic cells showed that macrophages were the most affected cells in the liver tissue 4 weeks after treatment 10 . This peptide does not have a direct inhibitory effect on inflammatory factors in macrophages, and it indirectly affects macrophages in vivo.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In this model, the reduction of liver damage was observed during the first week of treatment, and the reduction of liver damage and improvement of fibrosis was observed in the second week. In addition, single‐cell RNA analysis of hematopoietic cells showed that macrophages were the most affected cells in the liver tissue 4 weeks after treatment 10 . This peptide does not have a direct inhibitory effect on inflammatory factors in macrophages, and it indirectly affects macrophages in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, single-cell RNA analysis of hematopoietic cells showed that macrophages were the most affected cells in the liver tissue 4 weeks after treatment. 10 This peptide does not have a direct inhibitory effect on inflammatory factors in macrophages, and it indirectly affects macrophages in vivo. This report indicates that HMBG1 has important antiinflammatory and fibrosis-improving properties, and we believe it is a new regeneration-inducing agent that can reduce damage and improve fibrosis in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on drugs that increase fibrinolysis are lacking. A recent study shows that the HMGB one peptide can induce fibrinolysis ( Nojiri et al, 2021 ). Drugs targeting extracellular matrix deposition anti-fibrosis and their research progress are summarized in Table 4 .…”
Section: Therapeutic Targets and Related Drugs For Nafldmentioning
confidence: 99%
“…54 MSCs treatment restores liver macrophage homeostasis to ameliorates the progression of liver diseases including acute liver injury, liver brosis, and cirrhosis. [55][56][57] . Consistently, different hUCMSCs infusion regimens were found to exhibit differential effects on macrophage homeostasis regulation ability, among which the T-B group could signi cantly down-regulate the M1/M2 macrophages ratio.…”
Section: Disscussionmentioning
confidence: 99%